Table of Contents

**Definition**: inverse mapping

z1⇐ z ⇐ z2

t = (z-z1)/(z2-z1)

scale = (1-t)*s1 + t*s2

x’=x/scale

y’=y/scale

z < z1 scale = s1

z > z2 scale = s2

**Call**: hfTaperZ(xt,z1,z2,s1,s2);

**Parameters**:

xt - point coordinates array to be changed

z1, z2 - end points of z-interval, z2 > z1

s1, s2 - scaling factors for end points

**Test file**: taper.hf

**Definition**: inverse mapping

x1 ⇐ x ⇐ x2

t = (x-x1)/(x2-x1)

scale = (1-t)*s1 + t*s2

y’=y/scale

z’=z/scale

x < x1 scale = s1

x > x2 scale = s2

**Call**: hfTaperX(xt,x1,x2,s1,s2);

**Parameters**:

xt - point coordinates array to be changed

x1, x2 - end points of x-interval, x2 > x1

s1, s2 - scaling factors for end points

**Test file**: taper.hf

**Definition**: inverse mapping

y1 ⇐ y ⇐ y2

t = (y-y1)/(y2-y1)

scale = (1-t)*s1 + t*s2

z’=z/scale

x’=x/scale

y < y1 scale = s1

y > y2 scale = s2

**Call**: hfTaperY(xt,y1,y2,s1,s2);

**Parameters**:

xt - point coordinates array to be changed

y1, y2 - end points of y-interval, y2 > y1

s1, s2 - scaling factors for end points

**Test file**: taper.hf